Analisis Kandungan Natrium pada Snack Asin Komersial dan Kontribusinya terhadap Asupan Garam Harian: Survei Pasar di Surabaya Timur: Analysis of Sodium Content in Commercially Salty Snack and its Contribution to Daily Salt Intake: A Market Survey in East Surabaya - Pradana, Meisya Ayu; Farapti, Farapti; Daud, Zulfitri ‘Azuan Mat (Universitas Airlangga, 2025)
Background: Nearly the entire global population consumes excessive sodium. A food in sodium is salty snacks. Excessive sodium consumption can cause health problems such as hypertension, heart disease, stroke, and obesity. Salty snacks are popular and are frequently consumed and favored by the public. Objectives: To identify various commercial salty snack products and analyze their sodium content as well as their contribution to daily sodium and salt intake. Methods: The study was conducted through a survey of 32 commercial salty snacks produced in Indonesia and labeled with nutrition information. Products were collected from three supermarkets in East Surabaya—Superindo, Indomaret, and Alfamart, using a convenience sampling method. The survey was only conducted on small or medium packages of each product brand and variant so was limited. Results: A total of 32 salty snack products were identified and categorized into chips, light snacks, sticks and crackers, and nuts. The highest sodium content was 1394,4 mg per 100 g found in the sticks and crackers, which accounted for 50% of the daily sodium requirement. The average sodium content in other categories ranged around 500 mg, fulfilling 20-30% of the daily sodium. Conclusions: Commercial salty snack products are widely available in the market and generally contain high sodium levels. Attention to nutritional labeling, particularly sodium content, is essential in managing daily sodium and salt intake. In addition, the implementation of regulations or legislation regarding sodium labeling restrictions on salty snack products in Indonesia is necessary.